2016
DOI: 10.3892/mmr.2016.5352
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin inhibits macrophage classical activation via downregulating interferon regulatory factor 5 expression

Abstract: Mangiferin is a natural polyphenol and the predominant effective component of Mangifera indica Linn. leaves. For hundreds of years, Mangifera indica Linn. leaf has been used as an ingredient in numerous traditional Chinese medicine preparations for the treatment of bronchitis. However, the pharmacological mechanism of mangiferin in the treatment of bronchitis remains to be elucidated. Macrophage classical activation is important role in the process of bronchial airway inflammation, and interferon regulatory fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…leaves found a marked reduction in IRF5 expression in macrophages stimulated with LPS/IFNγ. This translated into a significant reduction in pro-inflammatory cytokine expression ( 136 ). How Mangiferin down-regulates IRF5 expression is not currently known.…”
Section: Current Therapeutic Strategies To Inhibit Irf5mentioning
confidence: 99%
“…leaves found a marked reduction in IRF5 expression in macrophages stimulated with LPS/IFNγ. This translated into a significant reduction in pro-inflammatory cytokine expression ( 136 ). How Mangiferin down-regulates IRF5 expression is not currently known.…”
Section: Current Therapeutic Strategies To Inhibit Irf5mentioning
confidence: 99%
“…Various reagents have been found to alleviate severe inflammatory reactions by interfering with IRF5. Mangiferin downregulates IRF5 expression, and therefore inhibits the activation of macrophages and the release of proinflammatory cytokines (13). Baicalin alleviates dextran sodium sulfate-induced colitis by decreasing LPS-induced IRF5 expression (14).…”
mentioning
confidence: 99%
“…Indeed, it was previously revealed that the IRF5 gene silencing suppressed levels of IRF5 in cardiac macrophages, reprogrammed their phenotype and supported the inflammatory resolution [58]. There are also some known IRF5 inhibitors [59], like TRIM28 or KAP1 [60], flavonoids called Baicalin (which simultaneously promotes M2 phenotype by IRF4 upregulation) [61] and Quercetin [62] or polyphenol called Mangiferin [63].…”
Section: Discussionmentioning
confidence: 99%